2018
DOI: 10.3390/molecules23112845
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,2-b]pyrazole-7-carboxamides Induce Apoptosis in Human Leukemia Cells at Nanomolar Concentrations

Abstract: Leukemia, the malignancy of the hematopoietic system accounts for 10% of cancer cases with poor overall survival rate in adults; therefore, there is a high unmet medical need for the development of novel therapeutics. Eight imidazo[1,2-b]pyrazole-7-carboxamides have been tested for cytotoxic activity against five leukemia cell lines: Acute promyelocytic leukemia (HL-60), acute monocytic leukemia (THP-1), acute T-lymphoblastic leukemia (MOLT-4), biphenotypic B myelomonocytic leukemia (MV-4-11), and erythroleuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…This result is consistent with that of previous studies; the candidate genes are reportedly linked to tumor cells. The change in ALOX5AP expression can cause oxidative stress, which has some effects on human leukemia [33]. Codreanu et al reported that ALOX5AP could be a noninvasive candidate biomarker for lung cancer with global and targeted proteomics [34].…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with that of previous studies; the candidate genes are reportedly linked to tumor cells. The change in ALOX5AP expression can cause oxidative stress, which has some effects on human leukemia [33]. Codreanu et al reported that ALOX5AP could be a noninvasive candidate biomarker for lung cancer with global and targeted proteomics [34].…”
Section: Discussionmentioning
confidence: 99%
“…The 4T1 cells were purchased from the ATCC (American Type Culture Collection, Manassas, VA, USA) and maintained as described previously [10]. Briefly, 4T1 were maintained in Roswell Park Memorial Institute 1640 medium (RPMI-1640) with 10% FCS.…”
Section: Real-time Cell Electronic Sensing (Rt-ces) Cytotoxicity Assaymentioning
confidence: 99%
“…Orthotopic transplantation of 4T1 cells offers a relevant tumor model to study efficacy of drug candidates or immune therapy regimens [8]. Previously, we showed the tumor promoting effect of mesenchymal stem cell (cancer associated fibroblast)-derived galectin-1 in the 4T1 model [9], and later on we screened an anti-cancer compound library of imidazo [1-2-b]pyrazole-7-carboxamides in both two-and three-dimensional cell cultures of 4T1 cells [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy-induced differentiation has been addressed in the late 1970s and still remained a therapeutic challenge to treat immature myeloid leukemias with high need for novel effective compounds [19]. We have previously synthetized a 67 member imidazo [1,2-b]pyrazole-7-carboxamide compound library with potent cytotoxic effect on HL-60 cells [20], and optimization of structure-activity relationship (SAR) resulted in the design of seven more active compounds [21]. These agents induced apoptosis in nanomolar range on HL-60 cells, but the way of action was not revealed.…”
Section: Introductionmentioning
confidence: 99%
“…These agents induced apoptosis in nanomolar range on HL-60 cells, but the way of action was not revealed. In order to explore the mechanism of action, our imidazo [1,2-b]pyrazole-7-carboxamide derivative, published earlier as DU325 [21], was further investigated to elicit its cytotoxic effect on human HL-60 and primary patient-derived AML cells.…”
Section: Introductionmentioning
confidence: 99%